FUN LEARNING FOR ISLAMIC LEARNERS: THE INFLUENCE OF FUN-BASED ENGLISH LEARNING ON SANTRI RESPONSES AT TPQ AT-TAQWA SUKADANA VILLAGE - Medisa Firdausi Nuzula; Audina Qurratul Aini; Rizki Fania; Multazam Ismail; Usuluddin (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to examine the influence of the Fun Learning for Islamic Learners method on santri responses toward English learning at TPQ At-Taqwa, Sukadana Village. The study was conducted within the framework of a community service program of Universitas Hamzanwadi. A quantitative pre-experimental design with a One Group Pre-Test Post-Test approach was employed, involving 25 santri aged 7 to 13 years selected through purposive sampling from a total population of 45 registered santri. Data were collected using a five-item Likert-scale questionnaire measuring santri responses across affective, cognitive, and behavioral dimensions, which was confirmed to be valid and reliable. The Wilcoxon Signed-Rank Test was applied as the primary analytical method following normality testing. The results indicate a statistically significant difference in santri response scores before and after the implementation of the Fun Learning for Islamic Learners method. The study concludes that fun-based, value-integrated English instruction is effective in improving the engagement and responsiveness of young learners in non-formal Islamic educational settings.